2017
DOI: 10.5194/isprs-archives-xlii-4-w4-117-2017
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Analysis on Land Surface Temperature in Urban Areas Using a Geographically Weighted Regression and Landsat 8 Imagery, a Case Study: Tehran, Iran

Abstract: ABSTRACT:Due to urbanization and changes in the urban thermal environment and because the land surface temperature (LST) in urban areas are a few degrees higher than in surrounding non-urbanized areas, identifying spatial factors affecting on LST in urban areas is very important. In this regard, due to the unique properties of spatial data, in this study, a geographically weighted regression (GWR) was used to identify effective spatial factors. The GWR is a suitable method for spatial regression issues, becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Other studies were conducted on the spatial distribution of LST in a small city in China or Korea (Buyadi et al 2013;Hu et al 2015;Babalola and Akinsanola 2016). Moreover, previous studies constructed only NDBI or NDVI to investigate the influence of land changes over LST (Karimi et al 2017;Xiong et al 2012;Pal and Ziaul 2017). Most studies only focused either on small cities or only one or two variables for assessing the impact of LST over land use.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies were conducted on the spatial distribution of LST in a small city in China or Korea (Buyadi et al 2013;Hu et al 2015;Babalola and Akinsanola 2016). Moreover, previous studies constructed only NDBI or NDVI to investigate the influence of land changes over LST (Karimi et al 2017;Xiong et al 2012;Pal and Ziaul 2017). Most studies only focused either on small cities or only one or two variables for assessing the impact of LST over land use.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, land surface temperature (LST) was considered to be equivalent to the temperature below the urban atmosphere and to be the primary factor in the analysis of surface radiation and energy variations, the inner climate of buildings, and human comfort in the urban environment. Physical features and color of urban surfaces, sky-view factor, street geometry, traffic lines, and human-made changes in nature are some of the essential factors that determine LST in urban environments (Deo & Şahin, 2017;Jiang & Weng, 2017;Karimi, Pahlavani, & Bigdeli, 2017). In this study, the data needed to model LST, were extracted from Landsat 8 satellite images.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers acknowledge that land degradation that is the change in land cover from vegetated land to open or built areas causes heating of air temperature and is a significant factor in increasing evapotranspiration. Land degradation also causes more runoff or surface flow than infiltration, and the increasing air temperature and surface flow will increase potential evapotranspiration (Karimi et al, 2017;Rushayati et al, 2018;Ping and Liu, 2018). In contrast, researchers also found that the deforestation process can also reduce evapotranspiration because of reduced transpiration by plants (Snyman, 2001;Feddema and Freire, 2001;Zeng and Yang, 2008;Li et al, 2013;Gong, 2017;Karimi et al, 2017;Rushayati et al, 2018;Ping and Liu, 2018).…”
Section: Analysis Of Evapotranspiration In Indonesian Tropical Areamentioning
confidence: 99%